Polymeric micelles and vesicles: biological behavior evaluation using radiolabeling techniques. (March 2014) - Psimadas, Dimitrios; Oliveira, Hugo; Thevenot, Julie; Lecommandoux, Sebastien; Bouziotis, Penelope; Varvarigou, Alexandra D.; Georgoulias, Panagiotis; Loudos, George
Abstract The application of combined diagnosis and therapy through nanotechnology applications is attracting increasing attention worldwide. Polymeric self-assembled nanoparticles (NPs) have been studied for this purpose. Micelles and vesicles with or without a magnetic core can efficiently carry diagnostic and/or therapeutic agents to a desired target. The biological behavior of these NPs has been evaluated in this study, after radiolabeling with 99mTc. In vitro stability, in media that mimic the environment of the living body, was better for vesicles than for micelles at 1 h and decreased for both as time passed. After administration to healthy animals, all NPs presented major uptake at liver and spleen as expected. Biodistribution and imaging studies confirmed the higher uptake in these organs for the hybrid NPs and at higher extent for the ones with larger size, indicating that the magnetic load and size play an important role on in vivo distribution.